PENGARUH KUALITAS PRODUK, KUALITAS LAYANAN, DAN LOKASI TERHADAP KEPUASAN PELANGGAN PADA RESTORAN NESTCOLOGY SEMARANG - Meilda Dwiki Kurniawan, 13.05.51.0109 (Students Journal of Economic and Management, 2017)
Along with the growth of the culinary business in Semarang, causing the higher level of competition which is faced by Nestcology. There are many kinds of consumer complaints which are given to Nestcology indicates that consumer satisfaction is not optimal. The purpose of this research is to analyze the effect of product quality, service quality and located on consumer satisfaction in Nestcology. This research tests three independent variables they are product quality service quality and located that can affect variable dependent it is consumer satisfaction. Population of this research are consumers of Nestcology. Samples were taken of 100 respondents by using non-probability sampling technique with the purposive sampling approach. Data was collected by using a survey method through quetionnaires which were filled out by consumers. Then, the data obtained were analyzed using multiple regression analysis. The result of indicate that variable product quality has the greatest influence on consumer satisfaction, followed by variable service quality. While variable product quality have an lowest influence compared to other variables. Keyword : product quality, service quality,located, consumer satisfaction